Hydrological dynamics in various agroecological zones and impacts of soil and water conservation measures on runoff and sediment yields in the Bale Eco-Region, Ethiopia - Berhanu, D.; Tarkegn, T. G.; Haileslassie, Amare; Alamirew, T.; Mekuria, Wolde; Zeleke, G.; Lemann, T.; Hurni, H.; Feyisa, G. L. (IWA Publishing, 2025)
The Bale Eco-Region (BER) in Southern Ethiopia is characterized by high surface runoff and sediment yield. This study assessed long-term (2016–2023) hydrological dynamics in three BER watersheds: Bekaye, Hawo, and Horosoba, exhibiting different agroecological zones and rainfall patterns. It investigated impacts of soil and water conservation (SWC) measures on runoff and sediment yield for Bekaye watershed, which experiences more intense rainfall than the others. Bekaye had a higher runoff coefficient (38.4%) and sediment yield (15.5 t ha−1 yr−1), while Hawo had lower values (19.6% runoff coefficient; 3.2 t ha−1 yr−1 sediment yield). Observation of significant differences in runoff coefficients and sediment yields highlights the influence of rainfall intensity, monthly rainfall distribution, topography, land use, and vegetation cover on hydrological and erosion processes. SWC interventions in Bekaye reduced runoff and sediment yield while increasing base flow in subsequent years. Results indicated that maintenance of SWC measures every two to three years following the implementation is key to sustaining their benefits in runoff and sediment reduction. This research provides novel insights into long-term hydrological dynamics under varying agroecological zones and rainfall patterns, offering a comprehensive assessment of SWC effectiveness in mitigating runoff and sediment yield.